Transcatheter embolization of a residual congenital coronary arteriovenous fistula with a detachable balloon; superiority of interventional cardiology? - Aydoğan, Ümrah; Dindar, Aygün; Ayhan, Yusuf İzzet; Tanman, Bahriye; Ertuğrul, Türkan; Ömeroğlu, Rukiye; Cantez, Talat (The Turkish Journal of Pediatrics, 1996)
A ten-year-old girl who presented with a continuous murmur was diagnosed with a right coronary to right ventricular fistula with colored Doppler echocardiography and selective arteriography. She underwent traditional treatment-ligation of the fistula by sternotomy. Afterwards, the systolic component of the murmur persisted and repeat arteriography showed a residual shunt through the fistula, with no change in the diameter of the right coronary artery. We describe the first case in which a residual fistula was treated with a detachable balloon embolization.
Keywords: interventional cardiology; arteriovenous fistula; fistula; coronary fistula